2012
DOI: 10.1016/j.jimonfin.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Sovereign bond yield spreads: A time-varying coefficient approach

Abstract: We study the determinants of sovereign bond yield spreads across 10 EMU countries between Q1/1999 and Q1/2010. We apply a semiparametric time-varying coefficient model to identify, to what extent an observed change in the yield spread is due to a shift in macroeconomic fundamentals or due to altering risk pricing. We find that at the beginning of EMU, the government debt level and the general investors' risk aversion had a significant impact on interest differentials. In the subsequent years, however, financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(80 citation statements)
references
References 42 publications
(29 reference statements)
6
72
1
1
Order By: Relevance
“…As can be seen, in all cases the marginal effects increase in the crisis period (β 1 ) compared to the pre-crisis period (β 1 + β 2 ). Therefore, these results are in line with previous studies that point out the dynamic properties of sovereign spreads drivers over time after the start of the crisis [see, e.g., Pozzi and Wolswijk (2008), Gerlach et al (2010), Aβmann and Boysen-Hogrefe (2012) and Bernoth and Erdogan (2012)] or which show an increase in the sensitivity of the price of risk to fundamentals during the euro area debt crisis compared with the pre-crisis period (see Beirne and Fratzscher, 2013, among them). Not only do all the variables that capture both local and regional fundamentals or market sentiment increase their significance in the two groups of countries in the crisis period compared to the pre-crisis one, but the variable that gauges global market sentiment also increases its significance after the start of the crisis in both central and peripheral EMU countries, confirming the increased importance of investors' risk aversion suggested by the literature [see Codogno et al (2003), Sgherri and Zoli (2009) To further investigate the possibility of differences in spread behaviour before and after the crisis period, we once again apply the general-to-specific approach, commencing from a general congruent specification that is simplified to a minimal representation consistent with the data evidence.…”
Section: Resultssupporting
confidence: 92%
“…As can be seen, in all cases the marginal effects increase in the crisis period (β 1 ) compared to the pre-crisis period (β 1 + β 2 ). Therefore, these results are in line with previous studies that point out the dynamic properties of sovereign spreads drivers over time after the start of the crisis [see, e.g., Pozzi and Wolswijk (2008), Gerlach et al (2010), Aβmann and Boysen-Hogrefe (2012) and Bernoth and Erdogan (2012)] or which show an increase in the sensitivity of the price of risk to fundamentals during the euro area debt crisis compared with the pre-crisis period (see Beirne and Fratzscher, 2013, among them). Not only do all the variables that capture both local and regional fundamentals or market sentiment increase their significance in the two groups of countries in the crisis period compared to the pre-crisis one, but the variable that gauges global market sentiment also increases its significance after the start of the crisis in both central and peripheral EMU countries, confirming the increased importance of investors' risk aversion suggested by the literature [see Codogno et al (2003), Sgherri and Zoli (2009) To further investigate the possibility of differences in spread behaviour before and after the crisis period, we once again apply the general-to-specific approach, commencing from a general congruent specification that is simplified to a minimal representation consistent with the data evidence.…”
Section: Resultssupporting
confidence: 92%
“…Hagen et al (2011) find that markets turned more sensitive toward fiscal measures after the collapse of Lehman Brothers. Bernoth and Erdogan (2012) also find evidence for timevarying coefficients that determine the impact of fiscal variables for the pricing of sovereign debt and for investors' risk aversion in a semi-parametric approach. Arghyrou and Kontonikas (2012) argue that the European sovereign debt crisis was in fact a currency crisis that diverted into markets for sovereign bonds.…”
Section: Relation With the Literaturementioning
confidence: 77%
“…2 Hagen et al (2011) and Bernoth and Erdogan (2012) document a sharp increase in risk aversion. See a detailed discussion below.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors, for example, Rommerskirchen (2016), argue that this is in fact what happened between 1996 and 2012. Other scholars have also observed that investors priced credit (or default) risk in the yields they demanded for financing the sovereign debt of euro area member states (Bernoth and Erdogan 2012;.…”
Section: The International Political Economy Of the Sovereign Debt Crmentioning
confidence: 99%